Men who overturned empires - "Tinker, Hugh" (London, 1987)
The impetus to write this book came to fruition when my old friend of many years. Bob Frykenberg, suggested I might like to give some lectures at the University of Wisconsin, Madison. He spelled out what he had in mind: not a formal course for students working on a limited filed, but a series in which we would hope to interest a wider audience.His sights were set on university faculty as well as students, and also the professional and political people who lived around the state capitol.
Keywords: Revolutionists History 20th Century